[Rezension von: Chris L. de Wet, Preaching bondage: John Chrysostom and the discourse of slavery in early Christianity] - Ritter, Adolf Martin (de Gruyter, 2016)
Chris L. de Wet: Preaching bondage: John Chrysostom and the discourse of slavery in early Christianity, Oakland (University of California Press) 2015, XIII + 329 S., ISBN 978-0-520-28621-4, $ 95